2017
DOI: 10.1186/s41155-017-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Homework self-regulation strategies: a gender and educational-level invariance analysis

Abstract: This study investigates the measurement invariance as a function of gender and educational level of the Homework Behavior Questionnaire (Ktpc), an instrument developed to assess students' homework selfregulation strategies. A sample of 1400 elementary and middle school students was used. Results of confirmatory factor analysis indicated a good fit of the theoretical model composed of three dimensions: planning, execution and evaluation of the homework completion. The results also provided evidence for the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…Iako učenice pokazuju blagu prednost u sedmom razredu s obzirom na strategije učenja u odnosu na učenike, ova se razlika nije pokazala statistički značajnom. Time nisu potvrđene pretpostavke o boljim strategijama učenja i samoregulaciji kod učenica niti su potvrđena dosadašnja istraživanja u kojima djevojčice i djevojke pokazuju bolje strategije učenja (Bidjerano, 2005;Cadime, Cruz, Silva i Ribeiro, 2017). Međutim, u nekim je radovima, u kojima su upitnici korišteni na općenitoj razini s obzirom na sve predmete, pronađena razlika u strategijama učenja u korist muških učenika (Niemivirta, 1997).…”
Section: Raspravaunclassified
“…Iako učenice pokazuju blagu prednost u sedmom razredu s obzirom na strategije učenja u odnosu na učenike, ova se razlika nije pokazala statistički značajnom. Time nisu potvrđene pretpostavke o boljim strategijama učenja i samoregulaciji kod učenica niti su potvrđena dosadašnja istraživanja u kojima djevojčice i djevojke pokazuju bolje strategije učenja (Bidjerano, 2005;Cadime, Cruz, Silva i Ribeiro, 2017). Međutim, u nekim je radovima, u kojima su upitnici korišteni na općenitoj razini s obzirom na sve predmete, pronađena razlika u strategijama učenja u korist muških učenika (Niemivirta, 1997).…”
Section: Raspravaunclassified
“…This issue is especially pressing when schoolchildren do their schoolwork at home. Their activities are described as "schoolchildren's independent extracurricular educational activities, designed and accompanied by a teacher in order to achieve the planned results in learning" (Uskova, 2019, p. 43), when children have to achieve mastery of courses presented in the form of text, thereby preparing for lessons at school (Cadime, Cruz, Silva, & Ribeiro, 2017;Göllner et al, 2017;Mora & Escardibul, 2018;Núñez et al, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…In previous studies, the researchers investigated assignment aspects for middle and high school, including how many assignments were completed, and the amount of time spent on assignments. The results show that students finishing assignments are likely to achieve high academic performance (Bembenuty & Zimerman 2003;Cadime, Cruz, Silva, & Ribeiro 2017;Falch & Rønning, 2012;Núñez et al 2014Núñez et al , 2015cPlanchard, Daniel, Maroo, Mishra, & McLean 2015;Rosário et al 2015a;Valle et al 2016;Xu, Fan, Du, & He 2017). Specifically, novice students with lower performance considerably improved academic attainment (Grodner & Rupp 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, novice students with lower performance considerably improved academic attainment (Grodner & Rupp 2013). Recent research has also revealed the reason for students completing assignment is that they want to get higher grades , and the more assignments students do, the better they do on exams (Cadime et al 2017;Núñez, Fernández, Rosário, & Epstein 2015). Moreover, doing assignments encourages students to manage their time and environment, take responsibility, and seek help from other people or sources (Xu 2010(Xu , 2011(Xu , 2014.…”
Section: Introductionmentioning
confidence: 99%